Modele ryzyka skreślenia z listy studentów na przykładzie studentów trybu niestacjonarnego - Jackowska, Beata; Wycinka, Ewa (Models of Risk Relegation Based on the Example of Extramural Students, 2009)
On the basis of observations made on the 2004/2005 cohort of extramural students of the Faculty of Management, University of Gdansk, there was made an attempt to identify risk factors of relegation. In order to estimate probabilities of relegation during semesters, we used logit and probit models. The significance levels were examined with the use of chi-square test and Akaike information criterion. As a goodness of fit criteria were used pseudo-R2 measures and accuracy coefficients (based on ROC curve). The probabilities of rejection for these semesters were also estimated with the use of actuarial estimator of proportion due to presence of censored data. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 487-493